Quality Control Emotions: Strategies for Managing Student Stress in Higher Education - Unzilah Khomairoh; Hefniy; Eka Diana; Zohaib Hassan Sain (Al-Qalam Institute, 2025)
Rising concerns over student mental health have positioned stress management as a critical issue in higher education institutions worldwide. This research aims to analyze effective strategies for managing stress among college students, with a focus on implementing effective emotional regulation. Student stress is often influenced by academic pressure, social life, and institutional demands, which can significantly affect mental well-being. This study employs a qualitative case-study approach, using in-depth interviews with selected students at a higher-education institution to explore their lived experiences of coping with stress. The collected data were analyzed using thematic analysis to identify recurring patterns in the emotional regulation strategies students applied when facing academic, social, and personal challenges. The findings reveal that effective stress management strategies include structured time management, the application of meditation and relaxation techniques, and strong social support from peers, family, and the surrounding environment. These approaches play a crucial role in reducing academic and social stress levels. The study contributes to the development of structured mental health support programs. It offers practical implications for higher education institutions seeking to enhance students’ emotional resilience and overall psychological well-being.